MACROANATOMICAL STRUCTURE VALVULA INTESTINALIS SILKY SHARK (Carcharhinus falciformis) (Jurnal Bioconcetta, 2019)
AbstractCarcharhinidae is the Ordo Selachimorpha, Elasmobranchii subclasses. One of the member of this family is Silky Shark (Carcharhinus falciformes). Intestinum of this shark has uniqueness, in part of intestinum which is form a folding called valvula intestinalis. The folding has role as widing surface of food absorbsing. The uniqueness of intestinum can be influed by habitat differencete ad ytpesof food consumtion. This aims of this study is to determined the structure macroanatomi of valvula intestinalis of Silky Shark (C. falciformes). Tester of this research obtained from Fish Landing (TPI) Wakatobi. Types of study is pure experiment. Data of morphology observation analised descriptively, to describe the tester of morphology character, where as macroanatomy of valvula intestinalis is decided by observing the variation of intestinum internal folding, number of folding, and scupe valvula surface. The observation result of macronatomy structure slimid that valvula intestinalis of Silky Shark (C. falciformes) scuped paper roll with opposite of cloaca. Total of roll paper are fine with scape both surface is 84.10 cm2.